Nudging Debtors to Pay Their Debt: Two Randomized Controlled Trials - Felix Holzmeister; Jürgen Huber; Michael Kirchler; Rene Schwaiger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We conducted two large-scale, highly powered randomized controlled trials intended to encourage consumer debt repayments. In Study 1, we implemented five treatments varying the design of envelopes sent to debtors. We did not find any treatment effects on response and repayment rates compared to the control condition. In Study 2, we varied the letters' contents in nine treatments, implementing factorial combinations of social norm and (non-)deterrence nudges, which were either framed emotively or non-emotively. We find that all nudges are ineffective compared to the control condition and even tend to induce backfiring effects compared to the agency's original letter. Since comparable nudges have been shown to be highly effective in other studies, our study supports the literature, emphasizing that the success of nudging interventions crucially depends on the domain of application.
Keywords: C93; D91; G51; 330; Nudging; randomized controlled trial; debt repayment